Effects of herbicides and fertility levels on weed dynamics and productivity of wheat (Triticum aestivum L.) - Dev, Ista; Singh, Raj Vir; Singh, Raghuvir; Dhyani, B.P.; Sengar, R.S.; Tomar, S.S.; Kumar, Dinesh; Kumar, Ajay (Annals of Agricultural Research, 2016)
A thrice replicated 2 year field experiment was conducted during Rabi seasions of 2013-14 and2014-15 to study the efficacy of various herbicides and fertility levels on weed dynamics andproductivity of wheat in a factorial randomized block design using F test. The results revealed thatamong the herbicidal treatments, post emergence application (30 DAS) of Clodinafop + Metsulfuron@ (60 g + 4 g ha–1) performed significantly better but statistically at par with two hand weedingswith respect to reduction in population as well as dry weight of weeds and obtained improved theplant height, dry matter accumulation, grain yield, straw yield and total NPK uptake, by wheatcrop. Likewise, 100% NPK + FYM 7.5 t ha–1 not only resulted in significantly increasing yield andnutrient removal, but also reduced weed population as well as their dry weight compared to othernutrient sources. Thus, 100% NPK + FYM @ 7.5 t ha–1 with Clodinafop + Metsulfuron @ (60 g + 4 gha–1) may be recommended for better weed management and higher wheat yield.